Phonemic Composition of Root Morphemes in the Old Byelorussian Language - Закарьян, М. (Kalbotyra, 1980)
The article deals with two questions: a) kinds of root morphemes according to their phonemic composition and b) variation of the phonemic composition of the root.The most wide-spread in the Old Byelorussian language is the root including one closed sylable. The root including an open syllable is typical only of verbs. The variation of the phonemic composition of the root creates various forms of morphs of one morpheme; the variation of the phonic composition – variants of morphs.